Hybrid impedance control of a robot manipulator for wrist and forearm rehabilitation: Performance analysis and clinical results - Akdogan, Erhan; Aktan, Mehmet Emin; Koru, Ahmet Taha; Arslan, M. Selcuk; Athhan, Murat; Kuran, Banu (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
Therapeutic exercises play an important role in the physical therapy and the rehabilitation. The exercises that can be assisted by a physiotherapist are increasingly being performed by the rehabilitation robots partially or fully due to their various merits. This study aims to develop a complete rehabilitation system, which consists of a rehabilitation robot, an HMI and a hybrid impedance controller that can model all the therapeutic exercises for an upper limb rehabilitation. The 3-DOF upper limb rehabilitation robot is able to perform the movements of flexion extension and ulnar radial deviation for the wrist, and the movement of pronation supination for the forearm. The experimental studies were conducted with healthy subjects and patients. First, the experiments were done with the healthy subjects to prove the control performance of the robotic system. The results showed that the hybrid impedance controlled robot can perform the therapeutic exercises very successfully. Then, the experimental studies were carried out with the real patients in a clinical environment. At the end of the treatment process, remarkable improvements were observed in terms of the limb force in all of the patients.
Keywords: Upper limb rehabilitation; Therapeutic exercise robot; Hybrid impedance control; EXOSKELETON; THERAPY; DESIGN; ARM; Automation & Control Systems; Engineering; Robotics